Respuestas

  • Usuario de Brainly
2013-03-04T02:40:54+01:00
f(-2) f(x) =x + 3 → f(-2) = -2+3 → f(-2) = 1

f(2) f(x) = x² - 9 → f(2) = 2² - 9 → f(2) = 4-9 → f(2) = - 5 f(1) f(x) = x + 3 → f(1) = 1+3 → f(1) = 4 ENTONCES
f(-2) = 1..........f(1) = 4............ f(2) = - 5


g(0)→ g(0) = -2.0² + 8.0 + 10 → g(0) = 10
g(5) →g(5) = -2.5² + 8.5 + 10 → g(5) = 5
g(9/2)→g(9/2) = -2(9/2)²+ 8(9/2) + 10 →g(9/2) = 11/2
g (11/2)→ g(11/2) = 11/2 - 5 → g(11/2) = 1/2

 

La respuesta esta completa!!!

 

salu2!!!!